Islamic (Sukuk) vs. Conventional Financing: Analysis of Profitability - Danish Ahmad Siddiqui; Falak Athar Khan (International Journal of Experiential Learning & Case Studies, 2018)
Over the last decade, Islamic Financials (Sukuk) emerged as a pioneering capital market instrument. One of the fundamental reasons for the emerging demand of Islamic Financing (Sukuk) includes its adherence to the finance in accordance to the Islamic values, avoiding Riba, which is the generation of money from money such as usury or interest. Sukuk issues have notably proliferated, which fuels the debate regarding the between the conventional and the Islamic finance. To investigate the impact of Islamic and Conventional Financials on shareholders’ wealth, this study takes the profitability ratios (including ROA, ROE, ROCE, and NPM) of 11 companies issuing Islamic Financials and 11 companies issuing Conventional Financials from the period between 2010 and 2015 and compares the profitability of both financials. The findings reveal the Islamic Financials (Sukuk) to be a significantly high source of profitability for a company along with the other clients’ catchy determinants such as religious principles, sharia-compliant instruments, and interest (Riba) free financing.